Pengaruh Rasio Daun Meniran (Phyllanthus Niruri), Teh Hijau (Camellia Sinensis) Dan Kayu Manis (Cinnamomum Burmanniic) Terhadap Kandungan Antioksidan Dalam Bentuk Herbal - Badruttamam, Ahmad; Puntri Pamungkas, Pinctada (Politeknik Negeri Ketapang, 2025)
Meniran (Phyllanthus niruri), green tea (Camellia sinensis), and cinnamon (Cinnamomum burmannii) are herbal ingredients known to have high antioxidant content. This study aims to determine the effect of variations in the ratio of the three ingredients on the antioxidant content in the form of herbal tea. The method used was a Completely Randomized Design (CRD) with three different formulations, namely F1 (30% meniran, 20% green tea, 50% cinnamon), F2 (20% meniran, 30% green tea, 50% cinnamon), and F3 (10% meniran, 40% green tea, 50% cinnamon). The analysis was carried out using the DPPH method to test antioxidant activity and organoleptic tests to assess taste, aroma, color, and texture. The results showed that the ratio of ingredients affected the antioxidant levels, with formulation F3 showing the highest antioxidant activity of 94.34 ppm. However, the ANOVA statistical test showed that the differences between formulations were not significant. Meanwhile, in terms of organoleptic, F1 has the highest score, especially in terms of aroma and color. The optimal combination is obtained from a balanced formulation between antioxidant effectiveness and consumer preferences.